2003
DOI: 10.1159/000070298
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of Apoptotic, Bcl-2, c-erbB-2 and p53 Tumor Markers in Salivary Gland Malignancies

Abstract: Objective: The clinical characteristics and survival probability rate of 36 patients with salivary gland malignancies and 10 patients with benign salivary tumors were summarized in relation to the immunohistological analysis of the tumor, apoptotic-related markers and apoptosis rate. The expression of the markers examined – Bcl-2, c-erbB-2, p53 – was detected in paraffin sections of the tumors by the streptavidin-biotin peroxidase method following heat-induced antigen retrieval, and the apoptosis rate was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…EGFR was shown to be involved in the pathogenesis of oral cancer (Nestor et al 2007), yet it was never studied in relation to either TUNEL or to phospho-Src family kinase which might be important with respect to further elucidating the pathogenesis of the disease. It has been demonstrated that this proto-oncogene ampliWcation and/or protein overexpression is associated with poor prognosis in breast carcinoma and other human neoplasms, including stomach, renal, pancreatic, ovarian and salivary gland carcinomas (Quenel et al 1995;Hanna et al 1999;Nagler et al 2003). Further credence for these results is found in the reported mutual pro-carcinogenic role for c-erbB-2 and phospho-Src family kinase, previously shown in other cancers (though never in oral SCC).…”
Section: Discussionmentioning
confidence: 89%
“…EGFR was shown to be involved in the pathogenesis of oral cancer (Nestor et al 2007), yet it was never studied in relation to either TUNEL or to phospho-Src family kinase which might be important with respect to further elucidating the pathogenesis of the disease. It has been demonstrated that this proto-oncogene ampliWcation and/or protein overexpression is associated with poor prognosis in breast carcinoma and other human neoplasms, including stomach, renal, pancreatic, ovarian and salivary gland carcinomas (Quenel et al 1995;Hanna et al 1999;Nagler et al 2003). Further credence for these results is found in the reported mutual pro-carcinogenic role for c-erbB-2 and phospho-Src family kinase, previously shown in other cancers (though never in oral SCC).…”
Section: Discussionmentioning
confidence: 89%
“…In this regard, it is interesting to note that previous studies found the level of positive TUNEL staining to be relatively high not only in salivary glands malignancies but also in oral cancer (Loro et al, 1999;Nagler et al, 1999Nagler et al, ,2003. Our results are also supported by multiple recent studies of various nonsalivary malignancies which demonstrated that high scores of Ki67 and p53 staining predict a higher tumourogenic grade, a higher rate of metastasis spread and a poorer prognosis, whereas low scores of Ki67 and p53 are associated with prognostically better histopathologic features (Saleh et al, 2000;Ben-Izhak et al, 2001Jalava et al, 2006).…”
Section: Discussionmentioning
confidence: 93%
“…The terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) assay (R&D Systems) was conducted on formalin-fixed and paraffin-embedded sections as previously described (18). An avidin-conjugated horseradish peroxidase bound to the biotinylated DNA fragments was used to generate a brown precipitate in the presence of diamenobezidine (Vector Laboratories Inc.).…”
Section: Terminal Deoxynucleotidyl Transferase-mediated Dutp Nick Endmentioning
confidence: 99%